PKCα promotes the mesenchymal to amoeboid transition and increases cancer cell invasiveness - Vaškovičová, Katarína; Szabadosová, Emilia; Čermák, Vladimír; Gandalovičová, Aneta; Kasalová, Lenka; Rösel, Daniel; Brábek, Jan (BMC cancer, 2015)
BACKGROUND: The local invasion of tumor cells into the surrounding tissue is the first and most critical step of the metastatic cascade. Cells can invade either collectively, or individually. Individual cancer cell invasion can occur in the mesenchymal or amoeboid mode, which are mutually interchangeable. This plasticity of individual cancer cell invasiveness may represent an escape mechanism for invading cancer cells from anti-metastatic treatment. METHODS: To identify new signaling proteins involved in the plasticity of cancer cell invasiveness, we performed proteomic analysis of the amoeboid to mesenchymal transition with A375m2 melanoma cells in a 3D Matrigel matrix. RESULTS: In this screen we identified PKCα as an important protein for the maintenance of amoeboid morphology. We found that the activation of PKCα resulted in the mesenchymal-amoeboid transition of mesenchymal K2 and MDA-MB-231 cell lines. Consistently, PKCα inhibition led to the amoeboid-mesenchymal transition of amoeboid A375m2 cells. Next, we showed that PKCα inhibition resulted in a considerable decrease in the invading abilities of all analyzed cancer cell lines. CONCLUSIONS: Our results suggest that PKCα is an important protein for maintenance of the amoeboid morphology of cancer cells, and that downregulation of PKCα results in the amoeboid to mesenchymal transition. Our data also suggest that PKCα is important for both mesenchymal and amoeboid invasiveness, making it an attractive target for anti-metastatic therapies.
Keywords: regulace genové exprese u nádorů; Cell Line, Tumor; invazivní růst nádoru; proteinkinasa C-alfa; Gene Expression Regulation, Neoplastic; Protein Kinase C-alpha; lidé; proteomika; signální transdukce; Signal Transduction; pohyb buněk; Proteomics; melanom; Mesoderm; mezoderm; Cell Movement; Neoplasm Invasiveness; nádorové buněčné linie; Melanoma; Humans